O pobre-diabo no centro do palco narrativo: uma leitura comparatista entre Dostoiévski e Graciliano Ramos - Rafaela Marra Melo (2019)
This Master’s thesis proposes a comparative study between the works Angústia, by Graciliano Ramos, and Notes from underground, by Fyodor Dostoevsky, taking in consideration the similarities and emphasizing the divergences that the brazilian “poor devil” lays with Dostoevsky’s “underground man”. The corpus analysis is made from a comparative, based on the concept of intertextuality, and an interdisciplinary perspective with the fields of history and sociology. Considering the works as creative synthesis of issues of the social life and the personal life of the authors, we investigate the historical panoramas and the social organizations from the 19th century of Russia and Brazil from the early 20’s and we make a brief incursion into the biographies of Graciliano Ramos and Fyodor Dostoevsky. Then, the narrative constructions of the “underground man” and the “poor devil” are studied, which allowed the comparison of the works, considered as intersections of constitutively dialogical texts, directing to the investigation of their similarities and differences and to the thought on what they have to say to us.